NOBEL PRIZE IN SCIENCES–2009 - Sharma, Archana (SCHOOL SCIENCE, 2010)
The prestigious Nobel award, instituted at the behest of the great scientist and the inventor of dynamite ‘Alfred Nobel,’ is tribute to persons who render most valuable service to humanity by their resolute and concerted work in different fields of physics, chemistry, physiology and medicine, economics and peace. The award is more than a mere symbol of recognition. The prize money of 1,66,000 US dollars is also of substantial help to individual scientists to carry forward research in their field of interest to satisfy their insatiable desire, in knowing the unknown for the benefit of mankind for which they have devoted their lives and effort. The Nobel Prize is an international award administered by the Nobel Foundation in Stockholm, Sweden. Like every year, the Nobel Prize for physics and chemistry for the year 2009 were announced by the Swedish Academy of Science while TheStockholm Faculty of Medicine recommended the awards for physiology and medicine.